2016
DOI: 10.1007/s00520-016-3287-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia, sarcopenia and biochemical markers in patients with advanced non-small cell lung cancer—chemotherapy toxicity and prognostic value

Abstract: Albumin level has been shown to be more important predictive marker of chemotherapy toxicity and survival than cachexia and sarcopenia are. This approach in clinical settings can be used to guide the choice of oncologic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…The results did not identify any statistically significant relationships between the presence of sarcopenia and any of the chemotherapy outcomes. These findings supported by larger study which included 100 NSCLC patients [25], however, are in direct contrast to other findings that have demonstrated a reduced disease response and increased treatment toxicities with the presence of sarcopenia [9,10] although these were also relatively small studies, both with sample sizes of 55.…”
Section: Discussionsupporting
confidence: 51%
“…The results did not identify any statistically significant relationships between the presence of sarcopenia and any of the chemotherapy outcomes. These findings supported by larger study which included 100 NSCLC patients [25], however, are in direct contrast to other findings that have demonstrated a reduced disease response and increased treatment toxicities with the presence of sarcopenia [9,10] although these were also relatively small studies, both with sample sizes of 55.…”
Section: Discussionsupporting
confidence: 51%
“…For advanced NSCLC, in addition to conventional cytotoxic chemotherapy, new molecular targeted drugs and cancer immunotherapy have revolutionized treatment. Sarcopenia is still controversial as a prognostic factor of cytotoxic chemotherapy for patients with advanced NSCLC [6][7][8][9]. Skeletal muscle index (SMI), but not skeletal muscle radiodensity (SMD), was a significant prognostic factor in an Italian study [9].…”
Section: Introductionmentioning
confidence: 97%
“…Following, Martin et al proposed SMI thresholds for sarcopenia in non-obese Caucasians according to sex and BMI (Martin et al, 2013) based on optimal stratification of SMI and survival; selected cut-off values were 43 and 53 cm²/m² in men with a BMI < and > 25 kg/m 2 , respectively, and 41 cm²/m² in women. Several further studies have demonstrated predictive value for toxicity (Sjøblom et al, 2015;Srdic et al, 2016;Stene et al, 2015;B. H. L. Tan et al, 2015), post-surgery complications (Lieffers, Bathe, Fassbender, Winget, & Baracos, 2012;P.…”
Section: Unsolved Questions Including Cut-off Issuesmentioning
confidence: 99%
“…Contrarily, eight studies showed no association between sarcopenia and chemotherapy toxicity (Blauwhoff-Buskermolen et al, Jung et al, 2015;Miyata et al, 2017;Palmela et al, 2017;Parsons, Tsimberidou, et al, 2012;Rollins et al, 2016;Srdic et al, 2016;Stene et al, 2015;Versteeg et al, 2017). One explanation could be that not all forms of chemotherapy exhibit sarcopenia-dependent toxicity, even if the studies were adequately powered to detect an association.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation